1991
DOI: 10.1037/0022-3514.60.6.870
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in sociosexuality: Evidence for convergent and discriminant validity.

Abstract: Individual differences in willingness to engage in uncommitted sexual relations were investigated in 6 studies. In Study 1, a 5-item Sociosexual Orientation Inventory (SOI) was developed. Studies 2, 3, and 4 provided convergent validity evidence for the SOI, revealing that persons who have an unrestricted sociosexual orientation tend to (a) engage in sex at an earlier point in their relationships, (b) engage in sex with more than 1 partner at a time, and (c) be involved in relationships characterized by less i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

45
1,095
8
67

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,205 publications
(1,215 citation statements)
references
References 60 publications
45
1,095
8
67
Order By: Relevance
“…Participants then saw an overview of these pictures and were asked which potential partner they would like to meet most, and how much they would like to meet this person. Finally, participants completed the Sociosexual Orientation Questionnaire (Simpson & Gangestad, 1991) as the individual differences measure of sexual motivation. This assessment occurred at the end of the study to prevent participants' from being suspicious about our research question.…”
Section: Methodsmentioning
confidence: 99%
“…Participants then saw an overview of these pictures and were asked which potential partner they would like to meet most, and how much they would like to meet this person. Finally, participants completed the Sociosexual Orientation Questionnaire (Simpson & Gangestad, 1991) as the individual differences measure of sexual motivation. This assessment occurred at the end of the study to prevent participants' from being suspicious about our research question.…”
Section: Methodsmentioning
confidence: 99%
“…During the recognition phase, faces appeared in randomized order. Finally, to assess participants' sociosexual orientation, participants completed the SOI (Simpson & Gangestad, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Sociosexuality is conceptualized as a personality dimension, with the poles labeled "restricted" (monogamous) sociosexuality and "unrestricted" (promiscuous) so-ciosexuality. On the basis of the observation that sociosexual behaviors, attitudes, and fantasies tend to correlate, Simpson and Gangestad (1991) developed the Sociosexual Orientation Inventory (SOI), a seven-item self-report questionnaire that combines measures of sociosexual attitudes, behaviors, and fantasies to an overall score. The SOI has been applied in over 40 published studies (reviewed in Simpson, Wilson, & Winterheld, 2004), including a largescale intercultural study that confirmed its reliability and validity across 48 nations (Schmitt, 2005).…”
Section: Sociosexualitymentioning
confidence: 99%
“…Sociosexuality is distinct from general sex drive or libido (Ostovich & Sabini, 2004) and unrelated to the interest to engage in sexual activity with a committed relationship partner (Simpson & Gangestad, 1991). Indeed, sexual motivation toward strangers appears to serve completely different functions than sexual motivation in committed relationships (Buss & Schmitt, 1993;Klusmann, 2002).…”
Section: Sociosexualitymentioning
confidence: 99%
See 1 more Smart Citation